Valoración económica del sistema de gestión integral de residuos sólidos urbanos en la ciudad de Sicuani – 2019 - Aguilar Larota, Jhon (2022)
Through this work we sought to quantify the economic valuation of the project of the management system for the management of solid urban waste of the population of the city of Sicuani. The scientific method was applied and a set of coherent and successive steps were followed to obtain reliable results, developing the deductive method with a quantitative approach that allowed a global analysis of the research phenomenon to identify its characteristics, from the whole to the parts; and to infer possible solutions; therefore, it was necessary to develop the research design without any manipulation of the variables, at the same time it was correlational. The population consisted of 1,314 households in the region under study. A survey was applied, which served as a means to test the hypotheses proposed. The willingness to pay was determined through an econometric model and computer tools were applied to process the information collected in order to analyze and interpret the data and quantify the economic valuation. The results pointed to the context of the economic reality of Sicuani, which, according to previous studies, has the availability to provide improvements in the solid waste management service.